The Healing Power of Nature: Integrating Ecology in to Counseling to Alleviate Student Stress - Budiyono, Alief; Zaman, Akhmad Roja Badrus; Nugroho, Adhitya Ridwan Budhi Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Madrasah students in urban environments often experience complex stress, while conventional counselling services are unable to provide effective and contextual solutions. This condition requires mental health interventions that can address students' emotional, psychological, and spiritual needs holistically. This study aims to analyze the effectiveness of ecological counselling services in reducing stress levels and increasing students' environmental awareness and adaptive capacity. This study used a mixed methods approach with an explanatory sequential design. The study subjects consisted of 20 students with high stress levels, who also served as subjects for the intervention trial. Data were collected through a student stress and well-being scale questionnaire and in-depth interviews. The research instruments were a Likert scale questionnaire and an open-ended interview guide. Quantitative data analysis was conducted using paired t-tests, while qualitative data were analyzed thematically. The results showed that ecological counselling effectively reduced student stress levels, as indicated by increased well-being scores. This counselling also built students' connectedness to their surroundings, strengthened resilience, and created a therapeutic space aligned with spiritual values. The conclusion of this study states that the ecological counselling approach can be a relevant intervention model for improving the mental health of madrasah students. This research has implications for integrating natural environmental elements in guidance and counselling services based on religious and cultural values.